Grammar of theology: logical argumentation from Origen to the Cappadocian Fathers - Usacheva, Anna (Vox Patrum, 2018)
The article outlines the philosophical and linguistic background of the Post- Nicene theological debates concerning the relationship between the Father and the Son. A sharp focus dwells of the provenance of the term hypostasis, the philosophical and grammatical understanding of the terms hypokeimenon and ousia and the Stoic definition of the signifier and thing signified. The article shows new aspects of the anti-Eunomian polemics of the Cappadocian fathers, which come into sight due to comparison of theological concepts with Hellenic linguistic and grammatical theories. In such a way, the comparison demonstrates methodological and technical strand of the theological argumentation of the Cappadocian fathers and their affinity for the exegetic methodology of Origen.